LATGALIAN JOKES: EXPRESSIONS OF LINGUISTIC CONTACTS - Kļavinska, Antra (Via Latgalica, 2012)
The research interest of the author of the article in the ethnosis living in Latgale, intercultural communication is related to the compilation of the entries for „Latgalian Linguo-Territorial Dictionary” with ESF project „Linguo-Cultural and Socio-Economic Aspects of Territorial Identity in the Development of the Region of Latgale” (Nr. 2009/0227/1DP/1.1.1.2.0/09/APIA/VIAA/071). The tasks of this research: 1) to prepare a review about the frequency of linguistic contacts and themes for conversations in jokes; 2) to determine the linguistic attitude of the addressee and the sender; 3) to trace linguistic processes in the event of intercultural communication.The theoretical background of the research is based on the speech act in theory (J. Searle), highlighting the impact of social and historical factors on the speech act (D. Hymes). In order to describe the results of linguistic contacts linguistic, social and historical factors shall be taken into consideration. Jokes (131 unit in total) have been selected according to the following components of the speech act: form of message – dialogue; sender and addressee – Latvians and non-ethnic Latvians (Russians, Poles, Jews, Gypsies, etc.) of Latgale and representatives of other regions; communication channel – oral and written communication; code – patois, dialect, language; theme – daily life, culture, religion, politics etc.; situation – Latgale of 20th century (episodically – Latvia, Russia, Germany, USA, Lithuania).The analysis of the expressions of language contacts in the texts of jokes lets conclude how intensive the mutual contacts of various languages and their users were in Latgale in the 20th century: if in the first half of the century the linguistic contacts were extremely diverse (interaction of Latgalian Latvians, Russians, Jews, Gypsies, Polish), then in the second half of the century mostly the linguistic contacts of Latvian (Latgalian) and Russian speaking population were domineering under the impact of the russification policy.The result of linguistic contacts are: 1) a tolerant attitude towards other languages and their users is typical for a Latgalian (character of jokes), but he/she has a negative position to an strange language (Latvian, Russian) as an expression of enforced power; 2) in the communication process one can observe intentional of code-switching and unintentional of code-mixing (basis of the comic: interlinguistic homonyms, homoforms); 3) linguistic interference: phonetic, lexical and grammatical borrowings (from Latvian, Russian, English); 4) foreign language skills (in the beginning of 20th century the modest foreigner language skills led to more frequent misunderstandings).The achievement of the aim put forward, result is a significant component of the speech act. The analyzed material of jokes proves that in many communicative situations this aim is not reached due to the weak communicative competence of the addressee and addresser (lack of awareness, understanding and recognition of the linguistic and cultural features of the representative of another ethos). Therefore, a conversation takes place, but an intercultural dialogue is not formed. Under current complex economic, political and linguistic situation in Latvia these are significant reasons for splitting of the society.